2000
DOI: 10.1002/1097-0320(20001215)42:6<327::aid-cyto1000>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Cytofluorometric methods for assessing absolute numbers of cell subsets in blood

Abstract: The enumeration of absolute levels of cells and their subsets in clinical samples is of primary importance in human immunodeficiency virus (HIV)؉ individuals (CD4؉ T-lymphocyte enumeration), in patients who are candidates for autotransplantation (CD34؉ hematopoietic progenitor cells), and in evaluating leukoreduced blood products (residual white blood cells). These measurements share a number of technical options, namely, single-or multiple-color cell staining and logical gating strategies. These can be accomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
200
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 206 publications
(206 citation statements)
references
References 179 publications
3
200
0
1
Order By: Relevance
“…This single-platform approach offers fewer sources of variability. Some earlier studies, however, have found a good correlation of these different methods (12,18).…”
Section: Values For Ab and CD T-lymphocytes In Healthy Adult Subjectsmentioning
confidence: 86%
See 1 more Smart Citation
“…This single-platform approach offers fewer sources of variability. Some earlier studies, however, have found a good correlation of these different methods (12,18).…”
Section: Values For Ab and CD T-lymphocytes In Healthy Adult Subjectsmentioning
confidence: 86%
“…A minimum of 30,000 events were measured. Absolute counts of circulating cell subsets were calculated using the percentages obtained by flow cytometry, and the leukocyte count was obtained from the hematological analyzer, using a dual-platform counting technology (18).…”
Section: Methods Of Analytical Determinationmentioning
confidence: 99%
“…This is achieved by the inclusion of fluorospheres as internal controls that allow precise cellular quantification and the adoption of a Lyse/No-wash flow cytometric protocol that prevents potential cell loss during washing steps (24). Although single-platform assays are routinely used in many clinical and research applications (25,26) their use in PBDC counting remains anedoctical (27,28). Because of the growing clinical relevance of PBDC assessment, we suggest that a single-platform approach should be largely applied to PBDC counting to improve the reliability of PBDC measurements.…”
Section: Discussionmentioning
confidence: 99%
“…16,18,19 At each step, cells were analyzed for percentage and viable absolute number of CD56 þ CD3 À , CD3 þ and by flow cytometry in single and dual platform approaches as described previously. 20,21 In case of a contaminating T-cell dose of X1.0 and o2.0 Â 10 5 /kg, the processed NK product was split into two units. In both centers, all patients received the NK-DLI unit freshly isolated at day þ 40 post HSCT; the next unit at day þ 100 was always cryopreserved.…”
Section: Patients and Conditioning Regimenmentioning
confidence: 99%